Automatic classification of Weevil-Infested Harum Manis mangoes using Artificial Immune Systems approach - Puteh, Saad; Hasnah, Ahmad; Yasmin, Yacob; Rafikha Aliana, A. Raof; Sabarina, Ismail (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 14th - 15th May 2005 at Putra Palace Hotel, Kangar. Perlis.